Pengembangan Desain Nail Art sebagai Representasi Legenda Danau Toba dalam Karya “The Enchanted Beauty of Toba” - Naomi Hasian; Ifa Nurhayati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This research aimed to develop a nail art design representing the Legend of Lake Toba in the work "The Enchanted Beauty of Toba." This research was motivated by the limited exploration of local culture-based nail art design development, particularly those featuring the Legend of Lake Toba. This research employed a quantitative approach with descriptive methods analyzed using percentage analysis. Data collection was conducted through sensory testing by three expert panelists and a questionnaire survey of 30 respondents, students of the Beauty Education Study Program, Faculty of Engineering, Semarang State University. The results showed that the sensory testing obtained an average score of 91%, categorized as "strongly agree," while the preference testing obtained an average score of 84%, categorized as "very like." These findings indicate that the developed design is not only technically valid but also acceptable to users. Thus, the nail art design based on the Legend of Lake Toba is proven to be able to represent cultural values ​​visually and symbolically in an innovative and aesthetic way.